ANALISIS PENERAPAN TATA TERTIB TERHADAP PEMBENTUKAN KARAKTER DISIPLIN SISWA DI SDN 5 KABILA - Ashrafiany Ashrafiany; Yane Hardiyanti Mahmud; Wartin S. Hamsah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
Elementary school education is not only oriented toward the transfer of knowledge, but also toward the formation of students' character, particularly discipline. This study aims to analyze the implementation of school rules at SDN 5 Kabila and their role in shaping students' discipline character. The research employed a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation during school activities. The findings show that school rules at SDN 5 Kabila have been formulated clearly and include essential aspects such as punctuality, neatness, classroom order, respectful behavior, and responsibility. Teachers play an active role in enforcing rules through supervision, habituation, modeling, educational sanctions, and positive reinforcement. Most students demonstrated disciplined behavior, such as arriving on time, wearing proper uniforms, and participating in lessons orderly. Nevertheless, some students were still inconsistent in obeying rules, particularly in punctuality and completeness of school attributes. The study concludes that consistent implementation of school rules, supported by teachers, parents, and the school environment, contributes positively to the formation of students' discipline character. Effective implementation requires routine evaluation, exemplary behavior from teachers, educational rewards and sanctions, as well as continuous habituation in daily school life.